Impact of forest biomass residues to the energy supply chain on regional air quality - Rafael, S.
The increase of the share of renewable energy in Portugal can be met from different sources, of which forest biomass residues (FBR) can play a main role. Taking into account the demand for information about the strategy of FBR to energy, and its implications on the Portuguese climate policy, the impact of energy conversion of FBR on air quality is evaluated. Three emission scenarioswere defined and a numerical air quality modelwas selected to perform this evaluation. The results reveal that the biomass thermal plants contribute to an increment of the pollutant concentrations in the atmosphere, however restricted to the surrounding areas of the thermal plants, and most significant for NO2 and O3.